Pengaruh Variasi Bahan Perekat terhadap Nilai Kalor dan Waktu Nyala Briket Arang Ban Bekas - Ali, Nurkiani Jail; Anas, Muhammad; Erniwati, Erniwati (Jurnal Penelitian Pendidikan Fisika, 2020)
This study aims to determine the effect of variations in binder on the heating value and burning time charcoal briquettes used tire. Charcoal briquettes were obtained in several steps, namely carbonization at a temperature of  350˚ for ±5 hours. Then grinding and sifting the charcoal with a size of 80 mesh. Mixing charcoal, binder and water,  this binder types used were starch, wheat flour and sago, and the percentage of binder material was 10% from total weight of charcoal powder. Mintage and pressing briquettes with a pressure of 100 kg/cm2. Drying under sunlight  for three days.  Briquettes  with starch binder  obtained Calorie Value 5181 cal/g. Calorie Value of the wheat flour binder is 4837cal/g and briquettes with sago binder obtained a Calorie Value of 3927cal/g. But the value of wheat flour and sago does not meet to Indonesia standard (Standar Nasional Indonesia/SNI) is 5000 cal/g. Result of the burning time test showed that the briquette burning time was 121 minutes on starch binder, 143 minutes of wheat flour and 148 minutes of sago.